Necesidad de reformar del art. 328 del código civil en relación a la terminación de la patria potestad del adoptante - Cruz Nogales, Javier Vinicio (2014)
Adoption is the legal act by which a family relationship between two people without the need for a blood tie through is created, is to receive as a child that is not naturally meet the requirements of the law. Custody is a parent-child relationship, as a protection regime unemancipated minors, where their protection is entrusted to their parents. Parental authority is not derived from the marriage contract, but is a right founded in nature and confirmed by law; that is, that parental authority is based on the natural father-child relationships, regardless of whether they are born within marriage or outside it. A legal effect to the completion of the adoption of Art. 330 of the Civil Code, for which, after the adoption, the former adopted, with their rights and obligations, shall be returned to his natural family, and failing that, will be placed in a suitable home or in an institution for the protection of minors prior favorable report of the Technical Unit Adoption Ministry of Social Welfare. Article 328 of the Civil Code states that parental rights of the adoptive parent is suspended or lost for the same reasons as that of the parent. But it is the case that says nothing in the Act, should terminate parental rights of the adoptive parent, because only indicates that the causes of the provisions shall be governed by the law for a parent. Two solutions fit: the child is emancipated and if it is even lower, receive a guardian to represent legally; or that parental return to its natural mother or father. In my view this solution should be considered in our law but with the nature of facultative, ie only regained custody father who can and wants it back and you trust him exercising the same judge or court that handled the adoption.